Hsa-miR-497-3p impedes the proliferation and invasion of triple-negative breast cancer cells by controlling epithelial-mesenchymal transition through ZEB1 targeting: Hsa-miR-497-3p inhibits triple-negative breast cancer cell proliferation - Dong, Qian; Chen, Hu; Li, Ying; Kong, Yan; Geng, Cuizhi; Liu, Yibing (Cellular and Molecular Biology, 2023)
This study aimed to examine the hsa-miR-497-3p effect and mechanism on the behavior of triple-negative breast cancer (TNBC) cells. We evaluated the expression of Hsa-miR-497-3p in tissue samples obtained from patients diagnosed with TNBC or luminal breast cancer (BrCa), utilizing the quantitative fluorescence polymerase chain reaction (PCR) method. We transfected hsa-miR-497-3p mimics and NC into MDA-MB-231 cells, whilehsa-miR-497-3p inhibitor and NC into TNBC cells, respectively. To examine the impact of hsa-miR-497-3p expression level on TNBC cell proliferation, invasion, and migration, we employed MTT, clone formation, Transwell, and wound healing assays. We utilized both q-PCR and western blot to validate the role of hsa-miR-497-3p in the epithelial-mesenchymal transition (EMT) of TNBC cells. To confirm the targeting relationship between hsa-miR-497-3p and ZEB1, we performed luciferase assays, q-PCR, and western blot analysis. We found that the hsa-miR-497-3p expression was down-regulated in both TNBC tissues and cell lines in comparison to luminal BrCa tissues and cell lines. Furthermore, hsa-miR-497-3p overexpression hindered the cell function of TNBC cells MDA-MB-231, while downregulating the mRNA and protein expression of vimentin and N-cadherin, while simultaneously upregulating E-cadherin expression. Our results demonstrate that hsa-miR-497-3p regulates EMT in TNBC cells through ZEB1 targeting, as evidenced by the modulation of the expression of vimentin, N-cadherin, and E-cadherin via ZEB1 inhibition. Overall, our study suggests that hsa-miR-497-3p inhibits the proliferation and invasion of TNBC cells through the modulation of EMT via ZEB1 targeting.